2022
DOI: 10.1093/hr/uhab075
|View full text |Cite
|
Sign up to set email alerts
|

The activation of gene expression and alternative splicing in the formation and evolution of allopolyploid Brassica napus

Abstract: Allopolyploids contain two or more sets of subgenomes. To establish a compatible relationship between subgenomes, a series of gene expression changes occurred in allopolyploids. What evolutionary changes of transcripts have taken place in Brassica napus during the early establishment and subsequent evolution was a fascinating scientific question. Here, we study this issue using a set of materials (natural, resynthesized B. napus and their progenitors/parents) by long-read RNA sequencing technology. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…A growing body of evidence have reported that SR protein encoding genes underwent AS events in response to environmental stresses in plants. For example, SR45a and RS2Z33 produced different isoforms to respond to drought stress in G. uralensis ( Li et al., 2022b ). A few SR genes were certificated to exhibit responsive AS patterns under heat, drought, and salt stress conditions in wheat ( Liu et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence have reported that SR protein encoding genes underwent AS events in response to environmental stresses in plants. For example, SR45a and RS2Z33 produced different isoforms to respond to drought stress in G. uralensis ( Li et al., 2022b ). A few SR genes were certificated to exhibit responsive AS patterns under heat, drought, and salt stress conditions in wheat ( Liu et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third-generation sequencing libraries were constructed by using the same plant materials used for ATAC-Seq with three biological replicates. The process of constructing RNA-Seq libraries can be found in our previous study 6 . Raw RNA-Seq data were filtered (length > 100, quality >7) by NanoFilt (v.2.5.0) to generate clean data.…”
Section: Methodsmentioning
confidence: 99%
“…Polyploidization brings two or more sets of identical or distinct genomes into a nucleus, producing either autopolyploids or allopolyploids 3 , which is accompanied by dramatic and dynamic genetic and epigenetic changes 3 5 , and allopolyploids have long been thought to play a more critical role in plant divergence due to unique hybridization during their formation 4 . Allopolyploids undergo more rapid and drastic transcriptional changes due to the sudden appearance of diverged subgenomes in the same cells 6 . Genomic expression dominance has been demonstrated to be a typical feature of many allopolyploids 7 , 8 , and a large amount of data has demonstrated that genomic expression dominance is associated with asymmetric epigenetic features, such as DNA methylation 8 , 9 , histone modification 8 and chromatin compactness 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternative splicing (AS) is a ubiquitous process to generate different transcripts from the same gene, which modulates the diversity of mRNA and gene expression ( Laloum et al., 2018 ; Li et al., 2022 ). Four major types of AS can be classified including intron retention (IR), alternative 3’ splice site (A3), alternative 5’ splice site (A5), and exon skipping (ES) ( Hu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%